Imagens, textos, ícones: análise dos arranjos visuais de livros didáticos de Geografia - Almeida, Daniela Gomes de (2018)
Taking as reference the importance of the Didactic Book for the teaching and learning processes of Geography, the historical changes in the profile of the students, as well as the new formats that these books present in the contemporary context, the general objective of this work is to analyze the visual arrangements in Geography textbooks. The corpus of analysis is constituted by the collection chosen by the greatest number of Geography teachers in the National Program of the Didactic Book of 2017 (PNLD / 2017), for the final years of elementary school (sixth to ninth grade), called "Expedições Geográficas". We adopted the hypothesis that the Geography textbooks are being restructured in terms of their formal aspects of the Graphic Editorial Project and its enunciated contents (Geographical and Pedagogical), from new iconic configurations, more inserted to the universe of the media and the hypertext layouts of the computer, proposing other ways of teaching Geography. As a way to understand these changes and graphic styles, we use the narratives of the authors of the works, obtained through a semi structured interview, showing their authorship perspectives and ways of producing textbooks. Thus, we try to analyze these new logics and possibilities of reading these objects. For the accomplishment of this work we use as a research methodology: the bibliographical revision, the documentary analysis and analysis of the narratives of the authors of the works. Based on observations from the Geographic Expeditions collection, we find that textbooks are changing, incorporating other languages, establishing communication bridges between print and hypermedia, converging languages, showing flexibility to the constructs and communicational processes of contemporaneity. These prerogatives meet the aspirations and features of students-teachers-school, demands of government public policies, which become legal and editorial requirements. In these injunctions, there are several tensions and conciliations: political, market and pedagogical. It is in this intersection of ways that the geography didactic books are analyzed.